2011
DOI: 10.1371/journal.pbio.1000620
|View full text |Cite
|
Sign up to set email alerts
|

Extinction Risk and Diversification Are Linked in a Plant Biodiversity Hotspot

Abstract: Plant extinction risks in the Cape, South Africa differ from those for vertebrates worldwide, with young and fast-evolving plant lineages marching towards extinction at the fastest rate, but independently of human effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
185
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(201 citation statements)
references
References 64 publications
13
185
3
Order By: Relevance
“…The high concentration of narrowly endemics at that region of the Espinhaço range may be an indicative of the presence of a pattern similar to that found by Davies et al (2011) We are grateful to the curators of CEN, HBG, NY, P, R, SPF and UB herbaria for providing access to the collec- ogy, chemistry, etc., and, thus, help us to propose stronger phylogenetic hypothesis, particularly for groups with poor resolution on lower levels, as observed in the DNA-based phylogenies of Chamaecrista and Mimosa (Borges et al Chapter 1;Conceição et al 2009;Rando et al unpublished data).…”
Section: H a P T E R T H R E Esupporting
confidence: 54%
“…The high concentration of narrowly endemics at that region of the Espinhaço range may be an indicative of the presence of a pattern similar to that found by Davies et al (2011) We are grateful to the curators of CEN, HBG, NY, P, R, SPF and UB herbaria for providing access to the collec- ogy, chemistry, etc., and, thus, help us to propose stronger phylogenetic hypothesis, particularly for groups with poor resolution on lower levels, as observed in the DNA-based phylogenies of Chamaecrista and Mimosa (Borges et al Chapter 1;Conceição et al 2009;Rando et al unpublished data).…”
Section: H a P T E R T H R E Esupporting
confidence: 54%
“…Although somewhat beyond the scope of the present work, we propose that the high extinction rates and declining speciation rates may be linked to the evolutionarily young ages of the groups in question and their presence in a biodiversity hotspot (i.e., the H-D Mountains; Myers et al, 2000;Wilson, 1992; http://www.biodiversityhotspots.org/xp/Hotspots; Richardson et al, 2001a,b). A recent study has shown that loss of biodiversity among recent clades in species rich areas is independent of anthropogenic effects and may be part of the natural, stochastic evolutionary course of such species (Davies et al, 2011). Future studies using Lilium-Nomcharis as a model system may seek to better understand the relationships among geomorphology, evolutionary rates, and extinctions within the Q-T Plateau and H-D Mountains regions.…”
Section: H-d Mountains and Its Correlation With Rapid Diversificationmentioning
confidence: 99%
“…Studies of several vertebrate groups [2][3][4][5][6][7][8][9] have found that taxa from older and species-poor lineages are most likely to face extinction. Davies et al [10] found the opposite pattern in South African plants: fast-evolving and speciose lineages are more prone to extinction. Selectivity in extinction risk could be explained by evolutionary history, represented by a clade's size and age.…”
Section: Introductionmentioning
confidence: 98%